2012
DOI: 10.1093/toxsci/kfs021
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Radiation Sensitivity of Recovery of Spermatogenesis Between Rat Strains

Abstract: Previous studies with Lewis/Brown-Norway (BN) F1 hybrid rats indicated that spermatogenesis was much more sensitive to ionizing radiation than in the widely studied outbred Sprague Dawley stock, suggesting that there were genetically based differences; however, the relative sensitivities of various inbred strains had not been established. As a first step to defining the genes responsible for these differences, we compared the sensitivities of seven rat strains to radiation damage of spermatogenesis. Recovery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 38 publications
4
14
0
1
Order By: Relevance
“…As shown previously (Abuelhija et al , 2012), there were large increases (~0.2 g) in testicular interstitial fluid in BN rats at 5 Gy of irradiation but small or negligible increases in SHR and SD rats. In all strains, the increases in interstitial fluid were dose-responsive (Fig.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…As shown previously (Abuelhija et al , 2012), there were large increases (~0.2 g) in testicular interstitial fluid in BN rats at 5 Gy of irradiation but small or negligible increases in SHR and SD rats. In all strains, the increases in interstitial fluid were dose-responsive (Fig.…”
Section: Resultssupporting
confidence: 87%
“…The present study clarifies the question of whether the data of our previous study (Abuelhija et al , 2012), showing that at 10 weeks after 5-Gy irradiation there was no recovery of spermatogenesis in BN rats, whereas in SHR and SD rats nearly all of the tubules contained differentiating germ cells, are a result of qualitative or quantitative differences between the strains. The dose-response studies showed that at 10 weeks after irradiation, BN rats failed to show recovery even after low doses (4 Gy) (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations